Ultrasonographic evaluation of the shoulder in elite Italian beach volleyball players - Monteleone, G.; Tramontana, A.; Mc Donald, K.; Sorge, R.; Tiloca, A.; Foti, C. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Beach volleyball is an overhead sport that subjects the hitting shoulder to intense functional loads. The purpose of this study is to identify ultrasonographically the prevalence of myotendinous alterations in professional Italian beach volleyball players at the Italian championship and to look for associations between ultrasound findings and the other data collected.